Perception of Tobacco Use and its Health Effects among Computer Professionals Working in a Private Institute - Singh, Neeti; Tamrakar, Nijina (Asian Journal of Medical Sciences, 2013)
Objectives: To understand the knowledge and perception of tobacco use, its health effects and the role of social responsibility on tobacco control among computer professionals. Material and methods: This is a descriptive study carried out on employees of a private information and technology institute in Kathmandu valley. Self administrated structured questionnaire was used for data collection after taking verbal consent. Statistical analysis was done using descriptive statistics. Results: Almost 93% of the participants had education level equivalent to bachelors degree or above. Majority had experienced tobacco use in their lifetime (95%). Among current users, 55% had tried to quit at least for once and when asked if they were happy to be tobacco users, interestingly 65.2% said they never thought about it. All the participants were aware of ill effects of tobacco on health. Eighty one percent associated it with cancer in any form while 57% thought tobacco use causes lung diseases. Majority of participants (62%) believed that tobacco products should not be easily accessible with banning of selling in grocer shops, banning advertisements and sponsorships of events by tobacco companies. With regard to their role as a social responsibilities towards tobacco free nation, major opinion expressed were not to use any form of tobacco, sharing their knowledge with others and stopping others from smoking at public places. Conclusion: There is need of lasting behavioral changing programs rather than awareness focused programs to control tobacco use among educated group who are aware of its ill effects. DOI: http://dx.doi.org/10.3126/ajms.v4i1.7460 Asian Journal of Medical Sciences 4(2013) 10-14